2021
DOI: 10.3390/polym13172915
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-pH Beverages on the Two-Body Wear of CAD/CAM Monolithic Materials

Abstract: The aim of this in vitro study is to evaluate the effect of different acidic media on volumetric wear and surface roughness of CAD/CAM monolithic materials. Forty-eight rectangular specimens were prepared using different CAD/CAM monolithic materials: nanohybrid composite (Grandio Blocks, Voco), resin-based composite (Cerasmart, GC), lithium disilicate (E-Max, Ivoclar), and high-translucency zirconia (Katana STML, Kuraray Noritake). After storage in distilled water at 37 °C for two days, the specimens were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Coffee is a mild acid with PH=5.8, composed of caffeine, tannic acid, citric acid, chlorogenic acid, while Coca-Cola is a strong acid with PH=2.5 composed of phosphoric acid, carbonated water, sugar, and caramel colour [15,16] . Dental restorative materials when exposed to the oral cavity may develop a change in colour and surface roughness, which is caused by a variety of reasons, including the type of the material, surface finishing, patient's dietary habits and oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee is a mild acid with PH=5.8, composed of caffeine, tannic acid, citric acid, chlorogenic acid, while Coca-Cola is a strong acid with PH=2.5 composed of phosphoric acid, carbonated water, sugar, and caramel colour [15,16] . Dental restorative materials when exposed to the oral cavity may develop a change in colour and surface roughness, which is caused by a variety of reasons, including the type of the material, surface finishing, patient's dietary habits and oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that their wear behaviour mostly consisted of delamination starting from wear facets [ 33 ]. Previous studies showed how the ZR delamination phenomenon seems to be more similar to the sound enamel wear mechanism, with several cracks regularly distributed throughout the entire extension of the wear pattern [ 34 , 35 ]. On the contrary, the LS group showed a more irregular surface and crack propagation pattern, both inside and outside of the wear scar’s area [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In today’s world, wear of restoration has become a common and serious problem. Restorative materials are exposed to a complex environment in the oral cavity, where they undergo severe chemical and physical stresses due to temperature changes, functional and parafunctional loads and chemicals from food and drinks [ 14 , 15 ], especially the erosive potential of acidic drinks [ 16 ]. To provide long-term stability, dental materials should demonstrate good wear resistance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%